2019
DOI: 10.1080/17445302.2019.1661625
|View full text |Cite
|
Sign up to set email alerts
|

Application of eddy-viscosity turbulence models to problems in ship hydrodynamics

Abstract: With the rapid advent of computational methods in all fields of engineering, several areas have emerged as significant sources of ambiguity. Among these is the selection of a turbulence model to close the Reynolds averaged Navier-Stokes equation. In ship hydrodynamics, this has been particularly difficult to resolve due to the complex nature of the problem. Furthermore, there are a wide variety of turbulence models all claiming superiority. Thus, navigating to the correct choice is a subject of experience. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…A verification study was conducted to assess the numerical uncertainties of the CFD models and to determine sufficient grid-spacing. The Grid Convergence Index (GCI) method based on the extrapolation of Richardson [49] was used to estimate the order of accuracy of the simulations, as similarly used by [50][51][52][53]. According to Celik et al [54] the apparent order of the method, , is determined by for a spatial convergence study of a 3D model.…”
Section: Verification Studymentioning
confidence: 99%
“…A verification study was conducted to assess the numerical uncertainties of the CFD models and to determine sufficient grid-spacing. The Grid Convergence Index (GCI) method based on the extrapolation of Richardson [49] was used to estimate the order of accuracy of the simulations, as similarly used by [50][51][52][53]. According to Celik et al [54] the apparent order of the method, , is determined by for a spatial convergence study of a 3D model.…”
Section: Verification Studymentioning
confidence: 99%
“…Firstly, shallow water flows are highly three-dimensional. As demonstrated recently by Terziev et al (2019b), the boundary layer of the ship is predicted to come in contact with the seabed in very shallow water cases. This brings about the second difficulty, referred to previously, namely, non-linear effects.…”
Section: Reynolds-averaged Navier-stokesmentioning
confidence: 67%
“…The present study will also serve to validate the assertion that the k -ω turbulence model provides good predictions over a greater range of case-studies. The expectation is that the resistance will be predicted with a small, negative error based on previous experience (Terziev et al, 2019b). The temporal term of the Navier-Stokes equations is discretised via a 1 st order accurate scheme, with a time-step of t=0.0035×L/V, following Tezdogan et al (2016).…”
Section: Reynolds-averaged Navier-stokesmentioning
confidence: 99%
“…Turbulence modelling is also a source of error in the results presented herein. Based on previous research, it is expected and indeed observed that the k-ω model has a tendency to underpredict resistance [31]. More sophisticated modelling approaches, such as those accounting for transition or those resolving large parts of the turbulent kinetic energy spectrum, should be used to assess the sensitivity of the adopted approach to turbulence modelling.…”
Section: Ship Resistancementioning
confidence: 98%
“…To account for turbulence within the fluid, the k-ω model of Wilcox [30] is used. This choice is made following previous work, which showed the particular model to be stable and provide the fastest solution time of all two-equation variants [31]. Benefits of using the k-ω model include its seamless application to low y + type meshes (y + < 1).…”
Section: Numerical Aspectsmentioning
confidence: 99%